Study of Coating Weight and Utilization Rate in the Modification of Ground Calcium Carbonate - Huiming Fan; Xueqin Wang; Jianan Liu; Binfeng Xu (BioResources, 2015)
Ground calcium carbonate (GCC) was modified in this work using starch, sodium stearate, and sodium hexametaphosphate. The effects of reaction temperature and the dosage of sodium hexametaphosphate on the coating weight of modified GCC and the utilization rate were considered. The strength (tensile, burst, and tear) of papers filled with modified GCC vs. unmodified GCC was compared. The research showed that lower precipitation reaction temperature was conducive to the increase of modified GCC coating weight and the complex utilization rate. A proper dosage of sodium hexametaphosphate could effectively increase the coating weight of modified GCC and the complex utilization rate. Compared with unmodified GCC filled papers, modified GCC filled papers performed better with respect to paper strength, but the optical properties (brightness and opacity) showed the opposite trend.